Creating a hierarchy of mental health stigma: testing the effect of psychiatric diagnosis on stigma. Issue 5 (26th September 2022) - Hazell, Cassie M.; Berry, Clio; Bogen-Johnston, Leanne; Banerjee, Moitree
Abstract : Background: Levels of mental health stigma experienced can vary as a function of the presenting mental health problem (e.g. diagnosis and symptoms). However, these studies are limited because they exclusively use pairwise comparisons. A more comprehensive examination of diagnosis-specific stigma is needed. Aims: The aim of our study was to determine how levels of mental health stigma vary in relation to a number of psychiatric diagnoses, and identify what attributions predict levels of diagnosis-specific stigma. Method: We conducted an online survey with members of the public. Participants were assessed in terms of how much stigma they had, and their attributions toward, nine different case vignettes, each describing a different mental health diagnosis. Results: We recruited 665 participants. After controlling for social desirability bias and key demographic variables, we found that mental health stigma varied in relation to psychiatric diagnosis. Schizophrenia and antisocial personality disorder were the most stigmatised diagnoses, and depression, generalised anxiety disorder and obsessive–compulsive disorder were the least stigmatised diagnoses. No single attribution predicted stigma across diagnoses, but fear was the most consistent predictor. Conclusions: Assessing mental health stigma as a single concept masks significant between-diagnosis variability. Anti-stigma campaigns are likely to be most successful if they target fearful attributions.